Meningkatkan Minat Belajar Pendidikan Agama Islam: Evektifitas Model Pembelajaran Kooperatif Talking Stick dalam Konteks Sekolah Menengah Kejuruan - mona agustina; Ahmad Fatoni; Robiyah Nur (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2025)
This study aims to analyze the effectiveness of the cooperative learning model Talking Stick in enhancing students' learning interest in Islamic Religious Education (PAI) at SMK Negeri 7 Bandar Lampung. The research employed a quasi-experimental design with a pretest–posttest approach involving 24 students. The learning-interest questionnaire instrument was validated, resulting in 12 valid items with a reliability coefficient of 0.861. The learning process was implemented through several sessions following the structured stages of the Talking Stick model and subsequently analyzed using statistical tests to examine significant differences between pretest and posttest scores. The findings indicate an increase in learning interest, particularly in student engagement, confidence in answering questions, and interest in PAI content. The novelty of this research lies in the application of the Talking Stick model to strengthen religious learning interest at the vocational high school level, as well as in improving the previously weak indicator of learning interest, namely “interest.” These findings contribute to the development of more engaging, collaborative activity-based instructional strategies for PAI that align with the characteristics of vocational students and effectively support the formation of religious attitudes and understanding.